2013
DOI: 10.1159/000354175
|View full text |Cite
|
Sign up to set email alerts
|

The Localized Inflammatory Response to Bronchoscopic Thermal Vapor Ablation

Abstract: Background: Bronchoscopic thermal vapor ablation (BTVA) reduces lung volumes in emphysema patients by inducing a localized inflammatory response (LIR) leading to a healing process of fibrosis, but may also increase symptoms. Objectives: We sought to evaluate whether the clinical manifestation of LIR correlated with patient outcome. Methods: Respiratory adverse events and inflammatory markers were analyzed from a multicenter trial of BTVA in patients with upper-lobe-predominant emphysema. End points including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 7 publications
0
36
0
1
Order By: Relevance
“…Following careful selection of the right patients, lung volume reduction may lead to clinically relevant improvements in lung function, quality of life, and exercise performance [7,8,9,10,11,12,13]. Of the available techniques, treatment with endobronchial valves (EBVs) in patients without interlobar collateral ventilation shows the best results [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Following careful selection of the right patients, lung volume reduction may lead to clinically relevant improvements in lung function, quality of life, and exercise performance [7,8,9,10,11,12,13]. Of the available techniques, treatment with endobronchial valves (EBVs) in patients without interlobar collateral ventilation shows the best results [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated a 48% target lobar volume reduction at 6 months after treatment, which was accompanied by improvements in lung function (140.8 ± 26.3 mL FEV 1 improvement, 17%), exercise tolerance (46.5 ± 15.0 m in the 6-minute walking test [6-MWT]), and quality of life (14.0 ± 2.4 point reduction in St. George’s Respiratory Questionnaire [SGRQ]) [3]. In a post hoc analysis, the occurrence and severity of serious adverse events increased with the volume of the treated lobe, with an inflection point identified at 1,700 mL target lobar volume [4]. Given the potential for improving the risk-benefit relationship on the basis of the above, an alternative approach was sought to limit the volume treated in a BTVA session, which has resulted in the design of the STEP-UP study [5].…”
Section: Clinical Evidence For Btvamentioning
confidence: 99%
“…However, the local inflammatory reaction seems to be essential for the desired lobar volume reduction. Patients who developed respiratory adverse events following BTVA experienced a better clinical outcome [46]. …”
Section: The Technologiesmentioning
confidence: 99%